Functional capacity testing in patients with pulmonary hypertension (PH) using the one-minute sit-to-stand test (1-min STST). - Christina Kronberger; Roya Anahita Mousavi; Begüm Öztürk; Robin Willixhofer; Theresa-Marie Dachs; René Rettl; Luciana Camuz-Ligios; Nima Rassoulpour; Christoph Krall; Brigitte Litschauer; Roza Badr Eslam (PLoS ONE)
Background The one-minute sit-to-stand-test (1-min STST) is a quick, space saving test to evaluate functional capacity. Exercise testing plays an important role in the long-term follow-up of pulmonary hypertension (PH) patients and is currently evaluated using the six-minute-walk-test (6MWT). The aim of the study was to assess the convergent validity of the 1-min STST in patients with PH and its association with markers of PH severity. Methods We evaluated 106 PH patients with the 1-min-STST and 6MWT and measured cardiorespiratory parameters (heart rate, blood pressure, oxygen saturation) before and after test conduction. N-terminal pro brain-type natriuretic peptide (NT-proBNP), WHO functional class (WHO-FC) and mean pulmonary artery pressure (mPAP) were defined as markers of PH severity. Results Strong correlation was found between performances of 1-min STST and 6MWT (r = .711, p < .001), indicating convergent validity. Both tests were inversely associated with NT-proBNP (STST: r = -.405, p < .001; 6MWT: r = -.358, p < .001), WHO-FC (STST: r = -.591, p < .001; 6MWT: r = -.643, p < .001) and mPAP (STST: r = -.280, p < .001; 6MWT: r = -.250, p < .001). Significant changes in cardiorespiratory parameters were observed in both tests (all p < 0.001). Further the post-exercise cardiorespiratory parameters correlated strongly between the 1-min STST and 6MWT (all r ≥ .651, all p < .001). Conclusion The 1-min STST demonstrated good convergent validity with the 6MWT and was associated with markers of PH severity. Furthermore, both exercise tests caused similar cardiorespiratory responses.